Interplay Between Inhibitory Control and Behavioural Flexibility: Impact of Dorsomedial Striatal Dopamine Denervation in Mice. (21st November 2021) - Lhost, Juliette; More, Simon; Watabe, Isabelle; Louber, Didier; Ouagazzal, Abdel-Mouttalib; Liberge, Martine; Amalric, Marianne
Highlights: DMS DA denervation disrupts sequential reversal learning. DMS DA denervation enhances perseverative and premature responses. DMS DA denervation disrupts proactive inhibitory control. Impaired inhibitory control may contribute to flexibility deficits in early PD. Abstract: In Parkinson's disease, nigrostriatal dopamine (DA) degeneration is commonly associated with motor symptomatology. However, non-motor symptoms affecting cognitive function, such as behavioural flexibility and inhibitory control may also appear early in the disease. Here we addressed the role of DA innervation of the dorsomedial striatum (DMS) in mediating these functions in 6-hydroxydopamine (6-OHDA)-lesioned mice using instrumental conditioning in various tasks. Behavioural flexibility was studied in a simple reversal task (nose-poke discrimination) or in reversal of a two-step sequence of actions (central followed by lateral nose-poke). Our results show that mild DA lesions of the DMS induces behavioural flexibility deficits in the sequential reversal learning only. In the first sessions following reversal of contingency, lesioned mice enhanced perseverative sequence of actions to the initial rewarded side then produced premature responses directly to the correct side omitting the central response, thus disrupting the two-step sequence of actions. These deficits may be linked to increased impulsivity as 6-OHDA-lesioned mice were unable to inhibit a previously learned motor response in a cued response inhibition task assessing proactive inhibitory control. Our findings show that partial DA denervation restricted to DMS impairs behavioural flexibility and proactive response inhibition in mice. Such striatal DA lesion may thus represent a valuable animal model for exploring deficits in executive control documented in early stage of Parkinson's disease.